Improving initial flattening of convex-shaped free-form mesh surface patches using a dynamic virtual boundary - Yavuz, Erdem; Yazıcı, Rıfat; Kasapbaşı, Mustafa Cem; Bilgin, Turgay Tugay (CRL Publishing admin@crlpublishing.co.uk, 2019)
This study proposes an efficient algorithm for improving flattening result of triangular mesh surface patches having a convex shape. The proposed approach, based on barycentric mapping technique, incorporates a dynamic virtual boundary, which considerably improves initial mapping result. The dynamic virtual boundary approach is utilized to reduce the distortions for the triangles near the boundary caused by the nature of convex combination technique. Mapping results of the proposed algorithm and the base technique are compared by area and shape accuracy metrics measured for several sample surfaces. The results prove the success of the proposed approach with respect to the base method. ©2019CRL Publishing Ltd.
Keywords: Barycentric mapping; Initial flattening; Surface parameterization; Triangular mesh; Virtual boundary